Etika Periklanan dan Perlindungan Anak dalam Iklan Mie Sedaap Papa Hidup Lagi - Burhanudin Al-Ghoni; Muhammad Shaba Shabira; Fajar Junaedi (MUKASI: Jurnal Ilmu Komunikasi, 2024)
In Indonesia's advertising context, upholding ethics is a crucial aspect for practitioners. The Indonesian Advertising Council recognizes the importance of ethics in creating advertisements that are not only creative but also ethical. As a strategic instrument in marketing communication, advertising must prioritize ethics when conveying messages to the public. Creating ethical ads requires specific methods to conform to established standards. This article evaluates ethical violations in the 'Papa Hidup Lagi' edition of Mie Sedaap's advertisement. This study will examine scenes that allegedly violate the advertising code of ethics in detail. This study uses a qualitative approach with content analysis techniques and data validity is strengthened with supporting related reference sources. Based on the research results, it was found that the 'Papa Hidup Lagi' edition of Mie Sedaap's advertisement violated Indonesian Advertising Ethics, especially Chapter. III A, article 3.1, sub-article 3.1.2 deals with depicting children in situations that are misleading or inappropriate to be shown. In addition, this advertisement violates the Chapter. III A, point 1.27 states that the benefits of a product must be conveyed honestly, correctly, and responsibly, and not add other benefits beyond the product's capabilities.